Stable drag reduction of anisotropic superhydrophobic/hydrophilic surfaces containing bioinspired micro/nanostructured arrays by laser ablation - Rong, Wanting; Zhang, Haifeng; Mao, Zhigang; Chen, Liang; Liu, Xiaowei (Colloids and surfaces. A, Physicochemical and engineering aspects, 2021)
Drag reduction using superhydrophobic surfaces is one of the most significant strategies to reduce energy consumption and drag losses in marine vessels and fluid channels. However, the trapped air at a solid-liquid interface on superhydrophobic surfaces usually becomes unstable under high flow speed impact, results the drag reduction effect is greatly reduced. Inspired by bionic fish scales, we propose asymmetric anisotropic superhydrophobic/hydrophilic surfaces (ASHS) simulating the asymmetric array structures of fish to improve the drag reduction ratios with a nanosecond laser ablation technology on aluminum-magnesium alloy. The alternated hydrophilic strips form a large surface energy barrier to strongly pin the three-phase contact line of air/water/solid for capturing air bubbles. ASHS presents different superhydrophobic properties along the positive parallel direction (PD) and the inverse direction (RD) parallel to the fish moving. Simulation models and a self-assembled solid-liquid interface friction test device can demonstrate the anisotropic drag reduction mechanism and test the drag reduction property in laminar flows. ASHS maintains a stable and improved anisotropic drag reduction effect at high speed (maximum 4.448 m/s). The study has provided promising applications in the fields of reducing energy consumption, liquid directional transportation, marine vessels. [Display omitted]